2016
DOI: 10.1111/acer.13276
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐Up of Alcohol Consumption After Liver Transplantation: Interest of an Addiction Team?

Abstract: This study highlights the clinical utility of a systematic addiction consultation among liver transplant patients, irrespective of the reason for transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Mandatory alcohol use screening of inpatients and in the emergency department effectively identifies heavy users, assists ALD diagnosis, and improves connection to treatment of AUD . Importantly, use of screening tools such as AUDIT has been shown to improve detection as well as the ability to predict long‐term clinical outcomes, including hospitalization for alcohol‐associated diagnoses …”
Section: Diagnosis Of Alcohol Use Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandatory alcohol use screening of inpatients and in the emergency department effectively identifies heavy users, assists ALD diagnosis, and improves connection to treatment of AUD . Importantly, use of screening tools such as AUDIT has been shown to improve detection as well as the ability to predict long‐term clinical outcomes, including hospitalization for alcohol‐associated diagnoses …”
Section: Diagnosis Of Alcohol Use Disordersmentioning
confidence: 99%
“…(33) Importantly, use of screening tools such as AUDIT has been shown to improve detection as well as the ability to predict long-term clinical outcomes, including hospitalization for alcohol-associated diagnoses. (34,35)…”
mentioning
confidence: 99%
“…(7) More recently, a French study confirmed the key role of the addiction specialist in identification of alcohol relapse. (8) These studies support a systematic evaluation of the addiction profile of LT candidates, regardless of how urgent transplantation may be. A multicenter evaluation of transplantation selection committees found that patients with ALD posed the most difficult dilemmas and that judgment among committees was highly inconsistent.…”
Section: See Article On Page 1310mentioning
confidence: 62%
“…An American study showed that clinical reports (especially from a psychiatrist) were the most reliable method to identify alcohol consumption . More recently, a French study confirmed the key role of the addiction specialist in identification of alcohol relapse . These studies support a systematic evaluation of the addiction profile of LT candidates, regardless of how urgent transplantation may be.…”
mentioning
confidence: 91%
“…Following transplantation, ALD patients return to consuming alcohol at charge similar to those transplanted for other reasons, even if ALD patients may consume better amounts 98 . As every transplant recipient's exhibit increased levels of alcohol assistance over time, post-transplant interventions are deemed enormously valuable in at the bottom of patients to maintain selfdenial 99 .…”
Section: Liver Transplantationmentioning
confidence: 99%